Incidence of symptomatic Covid‐19 infections in patients with mastocytosis and chronic myeloid leukemia: A comparison with the general Austrian population. (17th October 2022) - Graf, Irene; Herndlhofer, Susanne; Kundi, Michael; Greiner, Georg; Sperr, Martina; Hadzijusufovic, Emir; Valent, Peter; Sperr, Wolfgang R.
Abstract: Background: The SARS‐COV‐2 (Covid‐19) pandemic has impacted the management of patients with hematologic disorders. In some entities, an increased risk for Covid‐19 infections was reported, whereas others including chronic myeloid leukemia (CML) had a lower mortality. We have analyzed the prevalence of Covid‐19 infections in patients with mastocytosis during the Covid‐19 pandemic in comparison to data from CML patients and the general Austrian population. Materials and Methods: The prevalence of infections and PCR‐proven Covid‐19 infections was analyzed in 92 patients with mastocytosis. As controls, we used 113 patients with CML and the expected prevalence of Covid‐19 in the general Austrian population. Results: In 25% of the patients with mastocytosis (23/92) signs and symptoms of infection, including fever ( n = 11), dry cough ( n = 10), sore throat ( n = 12), pneumonia ( n = 1), and dyspnea ( n = 3) were recorded. Two (8.7%) of these symptomatic patients had a PCR‐proven Covid‐19 infection. Thus, the prevalence of Covid‐19 infections in mastocytosis was 2.2%. The number of comorbidities, subtype of mastocytosis, regular exercise, smoking habits, age, or duration of disease at the time of interview did not differ significantly between patients with and without Covid‐19 infections. In the CML cohort, 23.9% (27/113) of patients reported signs and symptoms of infection (fever, n = 8; dry cough, n = 17; sore throat, n = 11; dyspnea, n = 5). Six (22.2%) of the symptomatic patients had a PCR‐proven Covid‐19 infection. The prevalence of Covid‐19 in all CML patients was 5.3%. The observed number of Covid‐19 infections neither in mastocytosis nor in CML patients differed significantly from the expected number of Covid‐19 infections in the Austrian population. Conclusions: Our data show no significant difference in the prevalence of Covid‐19 infections among patients with mastocytosis, CML, and the general Austrian population and thus, in mastocytosis, the risk of a Covid‐19 infection was not increased compared to the general population.